Dental management of epileptic patient - Ledesma, Ma. Luisa C.
This case report involves an 11 year old female patient referred by OPD-UERM Pediatric Dentistry Division of the Philippine Children's Medical Center for evaluation and management. She was diagnosed as having congenital hydrocephalus with meningomyclocode with epileptic seizure. The etiology, classification, ethical manifestations, prognosis and treatment of the patient with epileptic disorder to render complete dental care for the patient will be presented. The developmental aspects of the disease as well as behavioral considerations will be reviewed.
Keywords: Epileptic seizure; Meningomyclocode; Congenital hydrocephalus